INTERCULTURALITY AND EDUCATION IN ARGENTINA. UNDERSTANDING CULTURAL DIFFERENCES IN THE EDUCATIONAL PROYECT (Andamios, Revista de Investigación Social, 2010)
The incorporation of the notion of interculturality since the 90’s in the state context has involved a new position of the State-nation towards indigenous people. Since then, the concept of interculturality —that became central within recognition policy— has been used in the educational field and developed new discourses and practices based on a new premise: the value of the “cultural diversity”. The new educational policy has recently incorporated that same premise, but this time in order to transform the neoliberal project based on the analysis of a new law in that area. The aim of this paper is to explore the discourse associated to the intercultural project in the new educational policy considering its theoretical implications and political consequences.
Keywords: State; education; discourse; interculturality; power